Dietary treatments enriched in olive and safflower oils regulate seric and placental matrix metalloproteinases in maternal diabetes - Martinez, Nora Alicia (2012)
Matrix metalloproteinases (MMPs) are proteolytic enzymes involved in placental development and function, although related to the pro-inflammatory environment when produced in excess. Previous studies have identified MMP-2 and MMP-9 overactivities in the placenta from diabetic rats. In this study, we aimed to determine whether diets supplemented with olive and safflower oil, enriched in natural PPAR ligands, are able to regulate MMP-2 and MMP-9 activities in the placenta and serum from diabetic rats. Diabetes was induced in rat neonates by streptozotocin administration (90 mg/kg s.c.). Control and diabetic rats were fed with 6% olive oil- or 6% safflower oil- supplemented diets from days 0.5 to 13.5 of gestation. On day 13.5 of gestation, placentas and sera were isolated for further determination of matrix metalloproteinases (MMPs) 2 and 9 activities by zymography. Placental MMP-2 and MMP-9 protein concentration and immunolocalization were also determined. Results Sera from diabetic pregnant animals showed MMP-2 and MMP-9 overactivities when compared to controls. Serum MMP-9 activity was significantly decreased when the diabetic animals received the olive and safflower oil dietary treatments. Placentas from diabetic rats showed increased MMP-2 and MMP-9 activities and protein concentrations, and both were decreased when diabetic rats received the olive and safflower dietary treatments. Conclusions This study demonstrates that both olive and safflower oil- supplemented diets were able to prevent MMPs overactivities in the placenta from diabetic rats, and that these beneficial effects are reflected in rat sera.